Pemanfaatan Batang Pisang menjadi Bahan Olahan Keripik sebagai Langkah Kreatif Kurangi Limbah dan Buka Peluang Usaha Baru di Desa Depok Kecamatan Bendungan Kabupaten Trenggalek - Aditia Gustiana Gunawan; Dilla Dientin Permatasari; Muhammad Farikh; Aries Theo Siallagan (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
The use of banana stems as a basic ingredient for chips is an innovative effort to reduce organic waste as well as open up new business opportunities for the people of Depok Village, Bendungan District, Trenggalek Regency. This topic of service was chosen because banana stem waste is generally unused and often becomes a source of environmental pollution. In fact, banana stems have great potential as an alternative food ingredient that can be processed into products of economic value. In this service, the methods used include the socialization stage, technical training, and production assistance to ensure the community's skills in processing banana stems into chips. The socialization stage was carried out to increase residents' awareness of economic opportunities from the use of local waste. At the technical training stage, residents are taught how to choose materials, processing processes, and packaging products so that they are suitable for sale. The results of the activity showed an increase in interest and skills of residents in producing banana stem chip products with various flavor variants. In addition, this product has managed to attract the attention of local consumers and has the potential to be marketed more widely. In conclusion, the use of banana stems into chips not only reduces environmental waste but also strengthens the community's economy through sustainable new business opportunities.